2011
DOI: 10.1208/s12249-011-9657-3
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the Accelerated Stability Assessment Program (ASAP) to Quality by Design (QbD) for Drug Product Stability

Abstract: An isoconversion paradigm, where times in different temperature and humidity-controlled stability chambers are set to provide a fixed degradant level, is shown to compensate for the complex, non-single order kinetics of solid drug products. A humidity-corrected Arrhenius equation provides reliable estimates for temperature and relative humidity effects on degradation rates. A statistical protocol is employed to determine best fits for chemical stability data, which in turn allows for accurate estimations of sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 11 publications
2
45
0
1
Order By: Relevance
“…The computer software (ASAPprime®) uses the isoconversion method (Waterman (2011)), rather than regression analysis to calculate the values of A, E a , B, where the isoconversion time, IC is the time to reach the predetermined value for the acceptance criteria (not less 80 % dissolved after 20 min). Replacement of the rate constant, k with the reciprocal of IC gives:…”
Section: Effects Of Temperature and Relative Humidity On Dissolutionmentioning
confidence: 99%
See 3 more Smart Citations
“…The computer software (ASAPprime®) uses the isoconversion method (Waterman (2011)), rather than regression analysis to calculate the values of A, E a , B, where the isoconversion time, IC is the time to reach the predetermined value for the acceptance criteria (not less 80 % dissolved after 20 min). Replacement of the rate constant, k with the reciprocal of IC gives:…”
Section: Effects Of Temperature and Relative Humidity On Dissolutionmentioning
confidence: 99%
“…1) in more complex, heterogenous systems, make the prediction of stability in solid dosage forms (SDF) more difficult. However, Waterman and co-workers (Waterman & Swanson 2014;MacDonald 2010;Colgan & Hofer 2015;Stella 2000;Timmerman 2003;Waterman 2011) have shown that the predominant factor that determines the rate of degradation in solid dosage forms, in addition to temperature, is the presence of water. That group has shown the rate of degradation of active pharmaceutical ingredients in tablets and other SDFs may be predicted using a modified Arrhenius equation (Eq.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For chemical stability assessment of drugs in the solid state, an Accelerated Stability Assessment Program or ASAP can be used, which is discussed in detail elsewhere in the literature (Waterman 2011). The ASAP method is based on an isoconversion concept that compensates for the complexity of solid-state degradation reaction kinetics and applies a moisture-corrected Arrhenius equation that explicitly takes into account the effect of relative humidity (RH) on the degradation rates in solid state (Waterman 2011).…”
Section: Introductionmentioning
confidence: 99%